Faktor risiko kejadian stunting pada balita di kota palopo - Nurlaeli Nurlaeli; Resty Ryadinency; Ayu Irawati (Darussalam Nutrition Journal, 2022)
Background: Stunting is a chronic condition showing a disruption of growth due to the last of ANC examination, breast milk not given exclusively, and toddlers not given the complementary feeding. Objective: To determine the factors contributing to the incidence of stunting in toddlers aged 12-36 months in the working area of Wara Public Health Centre, Palopo in 2020. Method: This study used an observational study method with a case-control approach. The population in this research was 96 toddlers in the working area of Wara Public Health Centre, Palopo in 2020, which is composed of 48 cases and 48 controls. Sampling technique used was a purporsive sampling. Data were collected through questionnaire. The data that had been collected then processed and assessed by using SPSS version 20 and analyzed using the odds ratio (OR) test and presented in the form of frequency distribution tables. Result: From the bivariate analysis, it was found out that risk factors research shows that the ANC history and the incidence of stunting (OR = 9.471), An exclusive breastfeeding history and incidence of stunting (OR = 3.975), and complementary feeding history and the incidence of stunting (OR = 5.160). Conclusion: The history of the ANC, a history of exclusive breastfeeding and history of Complementary Feeding are the risk factors for stunting in the working area of Wara Public Health Centre, Palopo in 2020. AbstrakLatar belakang: Stunting merupakan kondisi kronis terganggunya pertumbuhan dengan pemeriksaan ANC yang tidak lengkap, ASI yang tidak diberikan secara eksklusif dan balita yang tidak diberikan MP-ASI. Tujuan: untuk mengetahui faktor risiko kejadian stunting pada balita usia 12- 36 bulan di wilayah kerja puskesmas wara kota palopo tahun 2020. Metode: Penelitian ini menggunakan metode penelitian observasional dengan pendekatan case control. Populasi dalam penelitian ini yaitu 96 balita di wilayah kerja puskesmas wara kota palopo tahun 2020, yang terdiri dari 48 kasus dan 48 kontrol. Variabel yang diteliti adalah Riwayat ANC, Riwayat ASI Eksklusif, dan Riwayat MP-ASI. Teknik pengambilan sampel yaitu purporsive sampling. Pengumpulan data melalui kuesioner. Uji statistik yang di gunakan adalah uji Chi-Square. Hasil: Hasil penelitian menunjukkan bahwa riwayat ANC dengan kejadian stunting (p = ,003, OR = 9,471), riwayat ASI eksklusif dengan kejadian stunting (p = ,003, OR = 3,975), dan riwayat MP-ASI dengan kejadian stunting (p = ,004, OR = 5,160). Kesimpulan: Riwayat ANC, riwayat ASI eksklusif dan riwayat MP-ASI merupakan faktor risiko stunting di wilayah kerja Puskesmas Wara Kota Palopo tahun 2020